2018
DOI: 10.1109/jtehm.2018.2883943
|View full text |Cite
|
Sign up to set email alerts
|

EMG Pattern Recognition Control of the DEKA Arm: Impact on User Ratings of Satisfaction and Usability

Abstract: The DEKA Arm has multiple degrees of freedom which historically have been operated primarily by inertial measurement units (IMUs). However, the IMUs are not appropriate for all potential users; new control methods are needed. The purposes of this study were: 1) to describe usability and satisfaction of two controls methods—IMU and myoelectric pattern recognition (EMG-PR) controls—and 2) to compare ratings by control and amputation level. A total of 36 subjects with transradial (TR) or transhumeral (TH) amputat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…The survey also asked several investigator‐generated items including whether or not respondents needed help from another person to perform daily activities, and if so, the number of hours of help required in a typical day. For additional details about the survey, see Resnik et al 24 …”
Section: Methodsmentioning
confidence: 99%
“…The survey also asked several investigator‐generated items including whether or not respondents needed help from another person to perform daily activities, and if so, the number of hours of help required in a typical day. For additional details about the survey, see Resnik et al 24 …”
Section: Methodsmentioning
confidence: 99%
“…As a baseline study, we investigated the body-powered 3D printed hands that were available online. Prosthetic hands that were controlled using pattern recognition of electromyographic (EMG) signals and other sensory feedback strategies were excluded in the investigation (Kuiken et al, 2016 ; Resnik et al, 2019 ).…”
Section: Openly Accessible 3d Printed Prosthetic Handsmentioning
confidence: 99%
“…Electromyography (EMG) from the residual forearm has been used to control commercially available and research-grade prosthetic arms (Kuiken et al, 2016 ; Hargrove et al, 2017 ; Ottobock, 2017 ; Touch Bionics Inc, 2017 ; Wendelken et al, 2017 ; George et al, 2018 ; Page et al, 2018 ; Perry et al, 2018 ; Mobius Bionics, 2020 ). Although research has demonstrated proportional control of multiple, independent degrees of freedom (DOFs) (Davis et al, 2016 ; George et al, 2018 ; Page et al, 2018 ), commercially available prostheses still suffer from a variety of limitations (Biddiss and Chau, 2007 ), including limited number of pre-determined grips (Touch Bionics Inc, 2017 ), temporal delay due to sequential inputs used to select grips (Ottobock, 2017 ; Mobius Bionics, 2020 ), fixed output force (e.g., from traditional classifier algorithms) (Resnik et al, 2018a ), extensive training that lasts days to weeks (Resnik et al, 2017 , 2018a , 2019 ), and non-intuitive methods of control [e.g., inertial measurement units (IMUs) on residual limb or feet] (Resnik et al, 2018b ; Mobius Bionics, 2020 ).…”
Section: Introductionmentioning
confidence: 99%